Investigating interactions between chloroquine/hydroxychloroquine and their single enantiomers and angiotensin‐converting enzyme 2 by a cell membrane chromatography method. Issue 2 (17th November 2021) - Jia, Qianqian; Fu, Jia; Liang, Peida; Wang, Saisai; Wang, Yamin; Zhang, Xin; Zhou, Huaxin; Zhang, Liyang; Lv, Yanni; Han, Shengli
Abstract: Chloroquine and hydroxychloroquine have been studied since the early clinical treatment of SARS‐CoV‐2 outbreak. Considering these two chiral drugs are currently in use as the racemate, high‐expression angiotensin‐converting enzyme 2 cell membrane chromatography was established for investigating the differences of two paired enantiomers binding to angiotensin‐converting enzyme 2 receptor. Molecular docking assay and detection of SARS‐CoV‐2 spike pseudotyped virus entry into angiotensin‐converting enzyme 2‐HEK293T cells were also conducted for further investigation. Results showed that each single enantiomer could bind well to angiotensin‐converting enzyme 2, but there were differences between the paired enantiomers and corresponding racemate in frontal analysis. R ‐Chloroquine showed better angiotensin‐converting enzyme 2 receptor binding ability compared to S ‐chloroquine/chloroquine (racemate). S ‐Hydroxychloroquine showed better angiotensin‐converting enzyme 2 receptor binding ability than R ‐hydroxychloroquine/hydroxychloroquine. Moreover, each single enantiomer was proved effective compared with the control group; compared with S ‐chloroquine or the racemate, R ‐chloroquine showed better inhibitory effects at the same concentration. As for hydroxychloroquine, R ‐hydroxychloroquine showed better inhibitory effects than S ‐hydroxychloroquine, but it slightly worse than the racemate. In conclusion, R ‐chloroquine showed better angiotensin‐converting enzyme 2 receptor binding ability and inhibitory effects compared to S ‐chloroquine/chloroquine (racemate). S ‐Hydroxychloroquine showed better angiotensin‐converting enzyme 2 receptor binding ability than R ‐hydroxychloroquine/hydroxychloroquine (racemate), while the effect of preventing SARS‐CoV‐2 pseudovirus from entering cells was weaker than R ‐hydroxychloroquine/hydroxychloroquine (racemate).